Fostering team resilience with servant leadership: A multi-level study of the construction industry - Ahmad N. Siddiquei; Saima Ahmad; Fahad Asmi (Acta Psychologica)
Construction project teams operate in demanding and high-pressure environments, necessitating the development of team psychological resilience to achieve project goals effectively. Using the conservation of resource theory, we propose team-level servant leadership as an enabling style that facilitates team resilience development, subsequently affecting project success (team-level) and organizational citizenship behavior (individual level). The multi-level data was collected from 70 construction teams with 549 members. The multi-level analysis was performed using Mplus. The results of our study reveal a positive and significant connection between servant leadership, project success, and organizational citizenship behavior. Additionally, team resilience mediated the link between servant leadership and project success and organizational citizenship behavior. This research offers practical insights for project managers to nurture sustainable work practices within the construction industry through servant leadership.